Effectiveness of Using QRIS Payment as a Digital Payment Solution in Coffee Shop Business (Case Study of Circle Coffee Medan Coffee Shop) - Rizky Ramadhan; Ahmad Afandi (Universitas KH. Abdul Chalim Mojokerto, 2025)
The use of QRIS at Circle Coffee can influence consumer interest in facilitating non-cash payments and increasing payment efficiency. Researchers in this study found obstacles that limit the use of non-cash payments by consumers, or the lack of understanding of the community and the general public about QRIS. The purpose of this study is to see the effectiveness of QRIS payments in coffee shop businesses. This study uses a qualitative approach with a case study type of research and is descriptive. This research was conducted in a cafe shop (Circle Coffee) in Medan. Data analysis was carried out through three stages, namely data reduction, data presentation, and conclusions. The results of this study indicate that the use of QRIS payments as digital payments in coffee shop businesses is very effective. This is supported by the large number of consumers who prefer to use QRIS rather than cash as a means of payment. This study also provides an understanding that our society still needs further education about the use of digital payments.